2021
DOI: 10.1016/j.jaip.2021.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Mepolizumab in Hypereosinophilic Syndrome: An Open-Label Extension Study

Abstract: What is already known about this topic? A phase III study demonstrated that compared with placebo, 4-weekly add-on mepolizumab (300 mg subcutaneously) reduced flares in patients with uncontrolled FIP1-like-1-platelet-derived growth factor receptor a (FIP1L1-PDGFRA)-negative hypereosinophilic syndrome (HES), with a positive benefiterisk profile.What does this article add to our knowledge? This open-label extension study found no new safety signals with mepolizumab treatment in patients with FIP1L1-PDGFRA-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
1
20
0
2
Order By: Relevance
“…Similarly, a phase III trial let to mepolizumab approval by EMA for FIP1-like-1-platelet-derived growth factor receptor α-negative HES, given subcutaneously at a dose of 300 mg every 4 weeks versus placebo, and added on HES therapy ( Roufosse et al, 2020 ). While as safe as standard of care, the proportion of patients experiencing 1 or more flares/withdrawing from the study was 50% lower with mepolizumab versus placebo, and the open-label extension of the trial confirmed long-term control of disease flares, blood eosinophil counts, plus reductions in corticosteroid use ( Gleich et al, 2021 ).…”
Section: Implications For Biological Therapies Of Eosinophilic-associ...mentioning
confidence: 90%
“…Similarly, a phase III trial let to mepolizumab approval by EMA for FIP1-like-1-platelet-derived growth factor receptor α-negative HES, given subcutaneously at a dose of 300 mg every 4 weeks versus placebo, and added on HES therapy ( Roufosse et al, 2020 ). While as safe as standard of care, the proportion of patients experiencing 1 or more flares/withdrawing from the study was 50% lower with mepolizumab versus placebo, and the open-label extension of the trial confirmed long-term control of disease flares, blood eosinophil counts, plus reductions in corticosteroid use ( Gleich et al, 2021 ).…”
Section: Implications For Biological Therapies Of Eosinophilic-associ...mentioning
confidence: 90%
“…[1][2][3][4][5] Based on this knowledge, IL-5etargeting treatment approaches have been developed in the past 2 decades. [6][7][8][9][10][11][12] Mepolizumab is a humanized monoclonal antibody that binds to IL-5 and blocks IL-5 effects, including IL-5einduced growth, survival, migration, and activation of eosinophils. Mepolizumab has been approved for treatment of severe eosinophil-related asthma, eosinophilic granulomatosis with polyangiitis, and HES associated with chronic rhinosinusitis with nasal polyps.…”
mentioning
confidence: 99%
“…For the latter group of HES, two clinical trials, NCT02836496 and NCT03306043, have demonstrated efficacy of mepolizumab without major safety issues, leading to the approval of the drug. 8,11,12 In these trials, mepolizumab reduced the frequency of flares, fatigue severity, corticosteroid doses, and eosinophil counts in patients with nonclonal HES. 8,11,12 Although the mechanism of drug action in cytokine-triggered (reactive) HES is obvious, it remains unclear whether the drug acts in all patient subsets and whether responses depend on (and thus can be predicted by) eosinophil counts or serum IL-5 levels.…”
mentioning
confidence: 99%
“…However, the OCS-sparing effect of these therapies has not been demonstrated in randomised controlled clinical trials and their use can be limited by adverse effects ( 13 15 ). The OCS-sparing effect of mepolizumab in severe eosinophilic asthma and EGPA is well-established ( 17 19 ) and there is emerging evidence of an OCS sparing effect of mepolizumab in patients with HES ( 20 , 21 ). In the 20-week open label extension of the 200622 study (205203/NCT03306043) a ≥50% reduction in OCS daily dose was achieved by 28% of patients using OCS during the first 4 weeks of the study ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The OCS-sparing effect of mepolizumab in severe eosinophilic asthma and EGPA is well-established ( 17 19 ) and there is emerging evidence of an OCS sparing effect of mepolizumab in patients with HES ( 20 , 21 ). In the 20-week open label extension of the 200622 study (205203/NCT03306043) a ≥50% reduction in OCS daily dose was achieved by 28% of patients using OCS during the first 4 weeks of the study ( 21 ). Mepolizumab may therefore offer the additional benefit of OCS reduction for patients requiring chronic or repeated courses of OCS.…”
Section: Discussionmentioning
confidence: 99%